Provide and Protect the Essential Components. Issue 5 (12th June 2020) - Heidorn, Brent
Abstract : This article takes a look at the current educational climate during the worldwide COVID-19 pandemic, specifically the place that physical education has during this time. It explores the importance of maintaining standards-based learning and the essential components of physical education.